A systematic literature review on the determinants of sustainability reporting systems. Issue 4 (April 2023) - Benvenuto, Marco; Aufiero, Chiara; Viola, Carmine
Abstract: In the last decade, the use of sustainability reporting as a tool for communicating and reporting on the performance of sustainability objectives by companies has led to a growing awareness of its value and development in the corporate world. Therefore, exploring this phenomenon for a better understanding and identifying its characteristic elements is important. This study aims to systematically review the literature to establish the distinctive elements of sustainability reporting and provide a complete theoretical framework that allows the classification of the drivers that are crucial for adopting sustainability reporting. Through the analysis, we describe the characteristic elements of sustainability reporting in a homogeneous and concise summary. The drivers that result, may prove useful not only in the context of non-financial reporting but also in encouraging adequate economic-business reflections that may inspire new research trajectories for scholars in this field.